The Rural-Urban Migration and its Socio-Economic Consequences: A Study on the Rayerbazar Area of Dhaka City - Islam, Sirajul; Papia, Mahmuda Jahan; Yesmin, Sabrina (International Journal of Publication and Social Studies, 2022)
Movement from villages to cities is a crucial issue for Bangladesh. It influences both urban and rural socio-economic conditions. This paper basically focuses the influences of movement from different rural areas to Rayerbazar area in Dhaka. The questionnaire survey is used to find out the required results. Researchers divide the reasons of rural-urban (RU) migration into four categories as; economic, social, political and personal. This paper shows economic impact and social impact of rural-urban migration. Structural Equation Model (SEM) shows that RU migration due to social, and economic reasons has positive economic impact but RU migration due to political and personal reasons has negative economic impact. RU migration for social and economic reasons have negative social impact but political and personal reasons have positive social impact. Internal movement is one of the biggest problems for Dhaka city which could be reduced by ensuring sufficient income generating opportunities in villages.